Return : Nationalizing Transnational Mobility in Asia - Toyota, Mika; Yeoh, Brenda S. A.; Xiang, Biao (Book collections on Project MUSE., 2013)
Since the late 1990s, Asian nations have increasingly encouraged or demanded the return of emigrants. In this anthology, cases of return migration in Asia provide the ground for rethinking relations between nation-states and transnational mobility.